Critical Ethnography as an Archival Tool: A Case Study of the Afghan Diaspora in Canada - Rokay, Moska (Archivaria, 2021)
Due to the limitations of existing archival theories and methodologies, there are few clear options that allow underrepresented and marginalized communities to represent themselves ethically, faithfully, and responsibly in their own voices in mainstream archival institutions. As a result, many of these communities lack knowledge and fundamental pedagogical resources about themselves and their history in Canada. Based on research from the author’s one-year master’s degree, this article uses a critical ethnographic framework and oral history interviews to understand the archival needs of a segment of the Afghan diaspora that has long been settled in Canada. The Afghan Canadian participants agreed that digital archives could provide a solution to the community’s dearth of knowledge and material about itself – its own histories and stories. The research demonstrates that a critical ethnographic framework can be applied as an instrument in the archives in order to understand the desires, identity-formation processes, and representations of a marginalized community to ensure faithful archival representation.